Analisis Pengaruh Total Aset, Leverage, Opini Audit, dan Ukuran Kap Terhadap Audit Delay (Studi Empiris Perusahaan Manufaktur terdaftar di Bursa Efek Indonesia periode 2012-2014) - Dewi, Riris Kusuma, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2016)
The purpose of this research is to analyze the factors that affect audit delay to the manufacturing companies listed on the Indonesia Stock Exchange. The examined factors of this research are total assets, leverage, auditor's opinion and the size of a public accounting firm as the independent variables, while audit delay as the dependent variables. Sampling technique employed in this study is the purposive sampling with the total sample of 177 companies. The data analysis uses multiple regressions. The result of the study shows that the total assets, leverage, and the auditor's opinion have significant influence towards audit delay, while size of a public accounting firm do not have influence towards audit delay.